Effect of the Sugarcane Bagasse Deacetylation in the Pentoses Fermentation Process - Lima, Cleilton Santos; Neitzel, Thiago; de Oliveira Pereira, Isabela; Rabelo, Sarita Cândida [UNESP]; Ienczak, Jaciane Lutz; Roberto, Inês Conceição; Rocha, George J. M. (Springer Nature, 2021)
Biomass alkaline deacetylation prior to acid pretreatment can be a promising alternative to reduce the toxicity of hemicellulosic hydrolysates and improve second-generation bioethanol production. In this paper, the effect of alkaline deacetylation of sugarcane bagasse on bioethanol production by Spathaspora passalidarum was evaluated. Sugarcane bagasse deacetylated hemicellulosic hydrolysate (DHH) was processed using the following sequence: (1) deacetylation (0.4%, w/v NaOH, 70 °C, 3 h) and (2) acid pretreatment (0.5% (v/v) of H2SO4, 140 °C, 15 min). Non-deacetylated, hemicellulosic hydrolysate (HH), was obtained applying only acid pretreatment (0.5% (v/v) of H2SO4, 140 °C, 15 min). Biomass deacetylation reduced the content of acetic acid and some phenolic compounds in the hydrolysate (DHH) compared to acid pretreatment (HH), which resulted in its low toxicity. Thus, the bioethanol production with DHH was of 16.92 g L−1, whereas only 1.3 g L−1 of bioethanol was obtained with HH fermentation. Deacetylation process provided a 13-fold increase in bioethanol production by S. passalidarum, showing that alkaline deacetylation followed by sulfuric acid pretreatment is a promising strategy to increase bioethanol production. This procedure provided a simple and practical alternative to the classic methods of detoxification of hemicellulosic hydrolysate from sugarcane bagasse.
Keywords: Bioethanol; Biomass; Detoxification step; Inhibitors; Spathaspora passalidarum